2022
DOI: 10.1042/ebc20210055
|View full text |Cite
|
Sign up to set email alerts
|

Engagement with video content in the blended classroom

Abstract: Blended learning is becoming the expected norm for core content delivery in many institutions. Pre-recorded videos in the form of screencasts are the primary delivery method, with students being asked to engage with the content in this medium. Usage is only likely to increase into the future as delivery moves away from traditional lectures and seminars. In this perspective, we look at the use of video material as a means of content delivery and how to help students engage with it. Theoretical literature around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In other research settings, instructional videos for teaching in higher education have also been shown to be an effective content delivery and pedagogical tool and cost-effective [17][18][19][20]. Instructional videos can help reimagine learning by presenting content in new ways yet offering engaging and high-value learning experiences in a web-based environment.…”
Section: Video Games and Instructional Videos As Pedagogical Toolsmentioning
confidence: 99%
“…In other research settings, instructional videos for teaching in higher education have also been shown to be an effective content delivery and pedagogical tool and cost-effective [17][18][19][20]. Instructional videos can help reimagine learning by presenting content in new ways yet offering engaging and high-value learning experiences in a web-based environment.…”
Section: Video Games and Instructional Videos As Pedagogical Toolsmentioning
confidence: 99%
“…There are numerous parallels between these two ways of thinking. BL is becoming increasingly accepted in many educational institutions as the norm for delivering core curricula (Smith & Francis, 2022). Higher education has also given BL much attention to increasing learning effectiveness and efficiency (Kelly et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…By engaging both these systems simultaneously, learners can better grasp and retain complex concepts. Additionally, video content can complement students' learning by allowing them to work at their own pace, review material at several points in their learning journey and reduce extraneous load, which can otherwise overload the working memory capacity and reduce the ability of the students to remember new material [8]. In 1969, Paivio [9] presented his dual coding theory, proposing Abbreviations AmS, ammonium sulphate; COVID-19, coronavirus disease 2019; CTML, cognitive theory of multimedia learning; ER, endoplasmic reticulum; IEX, ion exchange chromatography; SEC, size exclusion chromatography.…”
mentioning
confidence: 99%